2018
DOI: 10.1007/s11892-018-0981-9
|View full text |Cite
|
Sign up to set email alerts
|

Family-Based Interventions Targeting Improvements in Health and Family Outcomes of Children and Adolescents with Type 1 Diabetes: a Systematic Review

Abstract: Twenty-five RCTs are reviewed. The majority of studies (n = 15) focused on interventions targeting both children and adolescents and their caregivers and were delivered in diabetes clinics, outpatient settings, mental health clinics, or participants' homes. Family-based interventions for youth with T1D appear effective at improving diabetes and family-centered outcomes. Additional research is needed to examine the pathways to improvement in glycemic control, as outcomes were mixed. Future research should also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 57 publications
2
41
0
3
Order By: Relevance
“…Previous systematic reviews of the literature and meta‐analysis indicate that a number of controlled studies have shown the efficacy of psychosocial and behavioral interventions for children and adolescents with diabetes, although this literature is not without some methodological limitations . Most of these interventions have included the family as an integral part of treatment …”
Section: Psychosocial and Behavioral Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous systematic reviews of the literature and meta‐analysis indicate that a number of controlled studies have shown the efficacy of psychosocial and behavioral interventions for children and adolescents with diabetes, although this literature is not without some methodological limitations . Most of these interventions have included the family as an integral part of treatment …”
Section: Psychosocial and Behavioral Interventionsmentioning
confidence: 99%
“…4,5,174,[177][178][179][180] Most of these interventions have included the family as an integral part of treatment. 181 The results of these studies indicate that family-based, behavioral procedures such as goal-setting, problem solving, self-monitoring, positive reinforcement, behavioral contracts, supportive parental communications, family restructuring, and appropriately shared responsibility for diabetes management have improved regimen adherence and glycemic control. 178,181,182 In addition, these interventions have improved the parent-adolescent relationship, 178,[183][184][185] and improved regimen adherence.…”
Section: Psychosocial and Behavioral Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…E ffective glycemic management in youth with type 1 diabetes (T1D) remains a significant challenge for families and diabetes care teams. [1][2][3] Although improved intensive insulin therapies that include continuous subcutaneous insulin infusion (CSII) 4,5 or the combination of CSII with real-time continuous glucose monitoring (CGM) (i.e., sensoraugmented pump [SAP] or sensor-integrated pump systems) 6,7 have been shown to improve clinical outcomes in young patients with T1D, many children and adolescents have not achieved the American Diabetes Association (ADA) or International Society of Pediatric and Adolescent Diabetes (ISPAD) standards of glycemic control. 8,9 Automated insulin delivery (AID) or closed-loop systems with algorithms that respond to real-time sensor glucose (SG) values to maintain euglycemia are, now, the forefront of technological therapies proposed to address the gaps in glycemic control.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of educational and behavioural interventions for adolescents with Type 1 diabetes have demonstrated some benefit in terms of glycaemic control; however, the feasibility of incorporating such interventions into clinical practice may be limited by healthcare resources and time, thus limiting scalability [3][4][5][6][7]. Text-messaging interventions have been studied in young people with Type 1 diabetes, and remain a practical and promising strategy [8][9][10].…”
Section: Introductionmentioning
confidence: 99%